Sustainable organizational development and reflection: A good combination? - Naudé, Marita (Virtus Interpress, 2012)
In the current global business environment companies continually face a range of very complex and multi-faceted challenges. Consequently, directors, members of corporate boards and managers need to implement innovative resources, capabilities and strategies to ensure both short and long term success and survival. One possible strategy is a tridimensional approach to Sustainable Development (SD) which includes economic, social and environmental dimensions at an equal level combined with practical SD initiatives, programs and strategies. In addition, reflection is a crucial skill in fast changing business environments as managers and practitioners who use reflection take more thoughtful, purposeful and value-driven action. The author accepts that reflection is a deliberate and complex analytical process to integrate knowledge with the demands of the situation as part of innovative practice, to integrate past experiences and consider influence of future hopes and fears to open a range of possible alternatives while simultaneously taking into account other people's perspectives. The paper highlights the possibility to combine SD and reflection and describes generic guidelines to enhance practical implementation and highlights both management and research implications relevant to a practical context.